2003
DOI: 10.1038/ncb1009
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of anchored proteins forms membrane diffusion barriers during neuronal polarization

Abstract: The formation and maintenance of polarized distributions of membrane proteins in the cell membrane are key to the function of polarized cells. In polarized neurons, various membrane proteins are localized to the somatodendritic domain or the axon. Neurons control polarized delivery of membrane proteins to each domain, and in addition, they must also block diffusional mixing of proteins between these domains. However, the presence of a diffusion barrier in the cell membrane of the axonal initial segment (IS), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
319
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 333 publications
(336 citation statements)
references
References 33 publications
16
319
1
Order By: Relevance
“…The observed elongated clusters and irregular domain boundaries suggest that line tension (and thus lipid fluid phase behavior) plays a limited role in domain shape (24), but interactions between the cytoskeleton and membrane proteins could certainly produce such a distribution of HA clusters within which lipids and proteins are confined but diffuse locally, such as has been suggested by Edidin, Kusumi, Vale, and others (16,17,26,27). Interdependence of raft protein trafficking, lipid second messengers, and the cytoskeleton merit further investigation (27)(28)(29).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The observed elongated clusters and irregular domain boundaries suggest that line tension (and thus lipid fluid phase behavior) plays a limited role in domain shape (24), but interactions between the cytoskeleton and membrane proteins could certainly produce such a distribution of HA clusters within which lipids and proteins are confined but diffuse locally, such as has been suggested by Edidin, Kusumi, Vale, and others (16,17,26,27). Interdependence of raft protein trafficking, lipid second messengers, and the cytoskeleton merit further investigation (27)(28)(29).…”
Section: Resultsmentioning
confidence: 92%
“…However, consensus on the existence, structure, size, and dynamics of rafts continues to be elusive because of disparate results obtained by a variety of methods (13). Instead, rafts are defined principally by biochemical means (14,15), and numerous biophysical models including lipid shells (5), temporary lateral confinement (16,17), preferential partitioning (18), and nanodomains (15,19) cannot be distinguished easily because they predict crucial structural details on length scales much smaller than the wavelength of visible light. Further distinction between these membrane models would provide insight into a large number of biological processes that depend on rafts (5,15,20).…”
mentioning
confidence: 99%
“…In particular, it has been shown that proteins in native membranes may not diffuse freely but are in fact confined to specific domains. Cells use several confining mechanisms such as anchoring to the cytoskeleton through hetero-bifunctional proteins (Byers and Branton, 1985), diffusion barriers formed by the accumulation of proteins anchored to cytoskeleton meshes (Halenda et al, 1987;Nakada et al, 2003), or self-assembly into large two-dimensional (2D) crystalline patches, as in the case of bacteriorhodopsin (bR), a light-driven proton pump found in the so-called purple membranes (PM) of Halobacterium salinarum (Blaurock, 1971). Despite these advances, an understanding of the membrane dynamics at the nanoscale remains a major challenge due primarily to the lack of measurement techniques allowing simultaneous spatial and temporal observation of single molecules within native membranes.…”
Section: Introductionmentioning
confidence: 99%
“…It is also addressed to physicists fascinated by the various spontaneous self -organization of lipids in water (lipid polymorphism) to warn them that lipids in biological systems are not always at thermal equilibrium, and that phase separations and lateral or transmembrane domains seen in model systems can differ fundamentally from biological situations. Indeed, molecule segregation in biological systems results often from the work of ATPases, like the fl ippases, or is the result of a molecule sorting by " protein gates " (see the " fence and picket model " of Kusumi and collaborators [2] ). Such mechanisms are diffi cult to mimic in model systems.…”
Section: Introduction XIII Historical Perspectives: Who Did What and mentioning
confidence: 99%
“…Why are there so many chemically different lipids coexisting in nature? (2) Why is the lipid composition of various membranes of eukaryotes different and sometimes even the two sides of biological membranes different (asymmetrical)? This requires numerous specifi c enzymes for the synthesis and ultimately for the shuttling to the right destination of newly formed lipids.…”
Section: Introduction XIII Historical Perspectives: Who Did What and mentioning
confidence: 99%